Preconcentration of some trace metal ions from drinking and tap water samples by sorption on amberlite XAD-4 after complexation with di-2-pyridyl ketone thiosemicarbazone - Asçi, B; Alpdogan, G; Sungur, S (TAYLOR & FRANCIS INC, 2006)
A method was established for enrichment of trace levels of Co(II), Ni(II), Fe(II), and Cu(II) ions in aqueous solutions. These metals were quantitatively retained on an Amberlite XAD-4 column, after complexation with di-2-pyridyl ketone thiosemicarbazone (DPKT). After elution with 1 M HNO3 in acetone, concentration of metals were measured by atomic absorption spectrometry. The effect of major cations of drinking and tap water samples on the sorption of metal ions also were investigated. The amount of the analyte metal ions determined after preconcentration was basically in agreement with the added amount. The developed method was used for the determination of trace amounts of metal ions in drinking and tap water samples with good results, such as relative standart deviations below 2% (N=6) and recoveries greater than > 95%.
Keywords: di-2-pyridyl ketone thiosemicarbazone; solid phase extraction; enrichment; column; AAS; cobalt; nickel; iron; copper; SOLID-PHASE EXTRACTION; ATOMIC-ABSORPTION-SPECTROMETRY; MULTIELEMENT PRECONCENTRATION; CADMIUM; 8-HYDROXYQUINOLINE; MEMBRANE; SEAWATER; LEAD; Chemistry